Characteristics of the Legislative Regulation of Participation of Representatives and Other Participants in the Civil Process - Krupchan, Olexander D.; Hryniak, Andrii B.; Pleniuk, Mariana D.; Lyubchik, Oleksandr A.; Talalai, Dmitriy V. (Cuestiones Políticas, 2020)
The relevance of the issues outlined in the article is due to the peculiarities of the legislative regulation of the participation of representatives and other actors in the civil process of Ukraine. In this vein, the purpose of the article is to scientifically prove that procedural representation differs significantly from representation in civil law, among other things, in the object and nature of the relationship that exists between the representative and the principal, thus as well as the legal grounds and consequences of both processes. Furthermore, it is observed that the specialist, unlike the expert, acts as an assistant and consultant to the court and does not carry out an independent investigation aimed at clarifying the relevant circumstances of the case. The main method of research on this topic was modeling, which allowed, among other things, to consider the civil process as the only organizational lawsuit that serves to resolve the life situation. It is concluded that the legislative participation model of representatives and other people aims to improve their professional skills aimed at strengthening the work of the judiciary, while managing and resolving various conflicts of different nature to guarantee social order.